Raman Suppression in a Kilowatt Narrow-Band Fiber Amplifier - 胡曼 杨依枫 郑也 刘广柏 王建华 刘恺 陈晓龙 赵纯 何兵 周军 (Chinese physics letters, 2016)
A novel technique to suppress stimulated Raman scattering in a high power narrow-band fiber amplifier is reported. By seeding with a comSination of a broadband amplified spontaneous emission seed and a narrowband master oscillator seed, the Raman Stokes components can be reduced about 16dB at a total output power of i kW. Ratnan suppression results are depicted in a different wavelengths seeding case and the same wavelength seeding ease, respectively, with different seed power ratios.